Monster Tales of Native Americans - Thorne, Ian.; Furan, Barbara Howell ([Mankato, Minn.] : Crestwood House, 1978)
A collection of monster stories from various North American Indian tribes.
Keywords: Indians of North America -- Legends; Animals, Mythical -- Juvenile literature; Monsters -- Folklore; Indians of North America -- Legends; Monsters -- Folklore; Animals, Mythical -- Folklore